PENGARUH PERSEPSI MASYARAKAT DAN FUNGSI PENGAWASAN BPD DALAM IMPLEMENTASI UNDANG-UNDANG NOMOR 06 TAHUN 2014 TETANG DESA TERHADAP AKUNTABILITAS ANGGARAN DI KECAMATAN TERAS KABUPATEN BOYOLALI - zulfa nisa'; edi santosa; lusia astrika (Journal of Politic and Government Studies, 2016)
ABSTRACTThe Accountability of Budgeting is a form to create a Good Governance. It’s form in thegovernment of the village relates on the role of the society and the controlling of BadanPermusyawarahan Desa, starting from the measure of planning which have to be appropriatewith what the goverment has done. The Accountability of Budgeting is very important for thesociety’s economic and financial walfare.Formulation of the problem in this research is ‘How is The Influences of The Society’sOpinions and BPD Controlling according to The Implementation of UU Nomor 06 Tahun 2014About The Village to The Accountability of Budgeting in Doplang Village, Teras Subdistrict ’.The method that is used in this research is mix method, which is a method that combinesqualitative and quantitative approach in the concern of methodology (same form as the dataaccumulation), and the study of a mix model which combines two approaches on the entireresearch.The population that is used in this research is people in Teras Subdistrict with twovillage as the samples, which is Doplang Village and Mojolegi Village. Starting from givingthem a quessionaire and an interview about the description that can give pictures of TheImplementation of UU Nomor 06 Tahun 2014 About The Village to The Accountability ofBudgeting in Teras Subdistrict, Boyolali Regency. There were 100 respondents and 6 informantsincludes the chiefs of BPD in Doplang and Mojolegi Village, the chiefs of Doplang and MojolegiVillage, a public figure and a member of BPD in Doplang Village.From the result of this research, the researcher concludes that the society’s opinionsaffect on the accountability of budgeting, where the people can do a control through the BPD astheir representative and controller. BPD itself has been quite great on doing it’s job incontrolling though there are obstacles that make the control less perfect. The suggestion thatcould be given is such as increasing BPD controlling, a need to make a good coordinationbetween the BPD and the government of the village by having a routine meeting that can be doneonce a month, supllying the amenities for BPD programs on doing it’s duties and give a specialattention for BPD welfare.Key words : Accountability, Budgeting, Badan Permusyawarahan Desa, The Society’sOpinions, Controlling.